A covalently bound inhibitor triggers EZH2 degradation through CHIP‐mediated ubiquitination. (20th March 2017) - Wang, Xu; Cao, Wei; Zhang, Jianjun; Yan, Ming; Xu, Qin; Wu, Xiangbing; Wan, Lixin; Zhang, Zhiyuan; Zhang, Chenping; Qin, Xing; Xiao, Meng; Ye, Dongxia; et al.
Abstract: Enhancer of zeste homolog 2 (EZH2) has been characterized as a critical oncogene and a promising drug target in human malignant tumors. The current EZH2 inhibitors strongly suppress the enhanced enzymatic function of mutant EZH2 in some lymphomas. However, the recent identification of a PRC2‐ and methyltransferase‐independent role of EZH2 indicates that a complete suppression of all oncogenic functions of EZH2 is needed. Here, we report a unique EZH2‐targeting strategy by identifying a gambogenic acid (GNA) derivative as a novel agent that specifically and covalently bound to Cys668 within the EZH2‐SET domain, triggering EZH2 degradation through COOH terminus of Hsp70‐interacting protein (CHIP)‐mediated ubiquitination. This class of inhibitors significantly suppressed H3K27Me3 and effectively reactivated polycomb repressor complex 2 (PRC2)‐silenced tumor suppressor genes. Moreover, the novel inhibitors significantly suppressed tumor growth in an EZH2‐dependent manner, and tumors bearing a non‐GNA‐interacting C668S‐EZH2 mutation exhibited resistance to the inhibitors. Together, our results identify the inhibition of the signaling pathway that governs GNA‐mediated destruction of EZH2 as a promising anti‐cancer strategy. Synopsis: Aberrant activation of PRC2 can block expression of key tumor suppressors and contribute to oncogenesis. The discovery of a drug that triggers specific degradation of PRC2 component EZH2 offers a new therapeutic strategy for cancer treatment. Derivatives of gambogenic acid (GNA) represent a new and unique category of EZH2 inhibitors. GNA‐derivatives bind covalently to EZH2, but not other methyltransferases, and trigger its degradation. The E3 ubiquitin ligase CHIP governs ubiquitination and destruction of EZH2 oncoprotein upon covalent binding of GNA derivatives. GNA derivatives efficiently inhibit cancer growth in vivo while showing little toxic side effect. Abstract : Aberrant activation of PRC2 can block expression of key tumor suppressors and contribute to oncogenesis. The discovery of a drug that triggers specific degradation of PRC2 component EZH2 offers a new therapeutic strategy for cancer treatment.